Development of adventure-based mental toughness inventory (ABMTI): need survey analysis among Malaysian active outdoor practitioners. / Mohd Shariman Shafie … [et al.] - Shafie, Mohd Shariman; Md. Taff, Md. Amin; Che Mat, Hisyam; Johanis, Nik Jazwiri; Mohd Said, Omar Firdaus; Hashim, Mustakim; Ab Aziz, Mohd Noorazlan; A. Rahman, Muhammad Wafi (Universiti Teknologi MARA, 2022)
A new landscape of adventure-based program demonstrated it linked to positive psychological aspects outcomes, including mental toughness. These benefits go beyond traditional character-building concepts of adventure-based programs. In Malaysia, there are numerous adventure-based programs conducted by many levels of organizations with aims to improve participants’ mental toughness. Unfortunately, there are very limited studies conducted on how to design a specific instrument of the adventure-based mental toughness program. The conceptual issues identified as main interest in this regard is identify the need to develop adventure-based mental toughness inventory among Malaysian outdoor practitioners. The study based on the Develop and Design Research (DDR; Saedah, Muhammad & Rozaini, 2020). IBM Statistic (SPSS) utilized as the main statistical analysis software. A total of 85 respondents (N=85) among active outdoor practitioners have purposively been selected. Based on the analyses, overall, 93% of agrees was achieved for all statements in the survey (with IQR= .0 -1.99). These findings provided a platform from which to foster coherent and systematic scholarly work on adventure-based program and mental toughness development.